BIBLIOMETRIC ANALYSIS OF STUDIES ON THE CONCEPT OF WORKPLACE INCIVILITY (Third Sector Social Economic Review, 2024)
Workplace incivility; refers to intolerant behavior such as disrespect, rude behavior, or unprofessional attitudes in a work environment. Such behaviors can occur in the workplace between employees or between employees and managers and can adversely affect the workplace atmosphere. In this study, it is aimed to revealing the effect of the study by visualizing the analysis of the research on ""workplace incivility"". A bibliometric analysis of the studies published in Web of Science (WOS) between 1999 and 2023 was analyzed with the VOSviewer (Version 1.6.9) package program. Since it was aimed at scanning the title, content, and keyword of the concept of ""workplace incivility"" in all languages and all publication types, analyzes were carried out, reaching 1,462 works. When we look at the year-based distribution, the year with the most publications is 2021, with 205 works. The most common publication type is a journal article with 1,302 works. The published works are in English, with a maximum of 1,451 works. In the study, when the most used keywords that had a relationship between them were analyzed at least twice, it was found that the most used keywords were workplace incivility with 210 repetitions, incivility with 301 repetitions, bullying with 109 repetitions, workplace bullying with 63 repetitions, and emotional exhaustion with 50 repetitions. This study is limited to the bibliometric analysis of studies published in WOS between 1999 and 2023. For future studies, research in databases such as PUBMed, Scopus, and TRDizin can be covered.
Keywords: Incivility; Workplace Incivility; Workplace Bullying; Mental Fatigue